Flipped Tutoring in Higher Education: Student Satisfaction with an Experience of Educational Innovation - González-Morga, Natalia (2024)
Introduction. University tutoring rarely includes innovative contributions that lead to new procedures to generate interest and have an impact on the university community. Objective. This paper analyzes student satisfaction with the experience of educational innovation based on flipped tutoring, focusing on the difference between initial expectations and final perception. Method. The research was based on a quantitative methodological approach and a non-experimental, descriptive, and longitudinal design. The participants in the study, 164 students from an Early Childhood Education, Primary Education, and Pedagogy degree, answered a valid and reliable questionnaire designed ad hoc. Results. The results showed student satisfaction with the employ of the tutoring method and the Kahoot platform. On the contrary, the students expressed dissatisfaction with the use of virtual forums. Conclusions. These digital tools offer pedagogical alternatives that facilitate the work of the tutor. Kahoot is perceived as a success in detecting training needs, while virtual forums require teacher reflection for their incorporation into flipped tutoring processes.